2020
DOI: 10.1073/pnas.2012249117
|View full text |Cite
|
Sign up to set email alerts
|

B cells reappear less mature and more activated after their anti-CD20–mediated depletion in multiple sclerosis

Abstract: B cell depletion via anti-CD20 antibodies is a highly effective treatment for multiple sclerosis (MS). However, little is known about the maturation/activation stage of the returning B cell population after treatment cessation and the wider effects on other immune cells. In the present study, 15 relapsing-remitting MS patients receiving 1,000 mg of rituximab were included. B, T, and myeloid cells were analyzed before anti-CD20 administration and in different time intervals thereafter over a period of 24 mo. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
51
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 34 publications
(39 reference statements)
10
51
3
Order By: Relevance
“…Recent research has improved the understanding on immunological characteristics of repleting CD20 + cells. A lately published study indicates that the reappearing pool of B cells after depletion with RTX mainly consists of naïve and transitional B cells, while memory B cells are diminished [103]. The same holds true for patients treated with RTX for various autoimmune diseases and for CD20 depletion in EAE induced with MOG peptide [102,[104][105][106].…”
Section: Repletion Of Cd20 + Cellsmentioning
confidence: 84%
See 1 more Smart Citation
“…Recent research has improved the understanding on immunological characteristics of repleting CD20 + cells. A lately published study indicates that the reappearing pool of B cells after depletion with RTX mainly consists of naïve and transitional B cells, while memory B cells are diminished [103]. The same holds true for patients treated with RTX for various autoimmune diseases and for CD20 depletion in EAE induced with MOG peptide [102,[104][105][106].…”
Section: Repletion Of Cd20 + Cellsmentioning
confidence: 84%
“…Since memory B cells are thought to be more pathogenic than naïve B cells, the observation of a more naïve repleting B cell pool seems to be a promising observation. However, repleting naïve B cells in patients with MS and RA were found to possess a more pro-inflammatory phenotype with variations of repopulation kinetics and patterns at an individual level [102][103][104]. More research is needed to find out whether rebound effects could occur after cessation of longterm anti-CD20 treatment.…”
Section: Repletion Of Cd20 + Cellsmentioning
confidence: 99%
“…In most patients, absolute blood B cell counts are still low six to nine months after infusion [ 127 , 128 ]. Interestingly, it was recently shown that in the reappearing B cell pool, the frequency of immature B cells and the expression of activation markers was found to be increased [ 129 , 130 ]. Mature plasmablasts and plasma cells are largely preserved as they lack CD20 expression [ 127 ].…”
Section: Current and Evolving Therapeutic Strategies In Nmosdmentioning
confidence: 99%
“…In addition to antibody production, B cells are important in antigen presentation and proinflammatory cytokine secretion [10]. The clinical success of anti-CD20 antibodies in the treatment of MS and NMOSD [11,12] underlines the important role of B cells in disease initiation and progression. Studies focusing on B cell subpopulations in MS and NMOSD are limited, and the precise role and changes in naïve and memory B cell distribution are still unclear in the development of MS and NMOSD.…”
Section: Introductionmentioning
confidence: 99%